Alpha and theta wave activation through pure crystal vibration on reducing anxiety in post-stroke patients with sleep disorders - Ida Zuhroidah; Mokh. Sujarwadi; Mukhammad Toha (KHD-Production, 2025)
Post-stroke patients often experience anxiety and sleep disorders that can hinder the recovery process. Improvement in sleep quality increases with decreasing anxiety; activation of alpha and theta waves can reduce anxiety. This study evaluates the effectiveness of pure crystal vibration waves in activating alpha and theta waves in decreasing anxiety, which has implications for improving sleep quality in post-stroke patients. This study used a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 30 post-stroke patients divided into two groups. Pure crystal vibration wave therapy intervention was given 30 minutes per day for 2 weeks in the treatment group; the control group was not given intervention. Anxiety was measured using the Hamilton Anxiety Rating Scale (HARS), and sleep quality was calculated using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using paired t-tests and independent t-tests. There was a significant decrease in anxiety scores (p = 0.001) and an increase in sleep quality (p = 0.001) in the intervention group compared to the control group. The frequency of pure crystal vibration waves effectively activates alpha and theta waves to indicate decreased anxiety, which has implications for improving the sleep quality of post-stroke patients.